Effect of ASF (a Compound of Traditional Chinese Medicine) on Behavioral Sensitization Induced by Ethanol and Conditioned Place Preference in Mice. (2nd November 2014) - Wen, Da-chao; Li, Yi-bei; Hu, Xiao-Yu; Lin, Wu; Jia, Ling-yan; Zhong, Sen
Abstract : ASF composed by semen and epimedium herbal is a traditional plant compound that is widely used in the treatment of insomnia. Studies have shown that saponins and flavonoids contained in semen can significantly decrease the content of excitatory neurotransmitter Glu in mice. And the total flavone of YinYangHuo can increase the release of GABA in the anterior periventricular system of rat and increase the affinity of GABA for the receptors GABAA. It can be inferred that their synergism may have effect on the neurotransmitter that causes behavioral sensitization and conditioned place preference in experimental animals and affects their drinking behaviors, which is the starting point of this research. The present study found that ASF can inhibit development and expression of behavioral sensitization induced by ethanol and the development of CPP in mice. We demonstrate the inhibition of ASF on behavioral sensitization partly due to its effect on the mesolimbic neurotransmitter system, including decreasing level of DA and Glu and increasing the content of GABA. It suggested that the ASF may have pharmacological effects in the treatment of alcohol addiction.